The Victorian soldier in Africa - Spiers, Edward M. (Studies in imperialism (Manchester, England), 2004)
This book re-examines the campaign experience of British soldiers in Africa during the period 1874-1902. It uses using a range of sources, such as letters and diaries, to allow soldiers to 'speak form themselves' about their experience of colonial.